Creating web pages simplified - Wooldridge, Mike Rao; Stuart, Brianna (Visual : read less-learn more, 2011)
In Creating Web Pages Simplified, readers get the building blocks needed to take them through all phases of Web publishing; from laying out and formatting text to enlivening pages with graphics and animation. This full-color, easy-to-follow guide is an indispensable tool for both first-timers and seasoned Web authors